2016
DOI: 10.1016/j.scitotenv.2016.05.160
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the CO2 dynamics in near-surface cavities under a future warming scenario: Factors and evidence from the field and experimental findings

Abstract: This study is based in a field monitoring of a cave-soil-atmosphere system validated with laboratory experimentation. CO2 and 222 Rn dynamics in the cavity demonstrate the dependence on the climatic parameters, mainly on the differences between outdoor and indoor temperatures. Within the cave, the annual cycles are characterized by two outstanding moments: cave gaseous recharge and ventilation when cave acts as gaseous sink or source respectively. Relationship with soil above the cave exists permanently. Soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…However, previous studies that examined the annual isotopic cycle (Pla et al, 2016a) The highest CO2 concentration observed as a direct consequence of the rainfall was achieved between March 28 and 29, some days after the last rainfall on March 24. After this last episode, soil VWC started decreasing but always remained higher than the value observed before the first rainfall episode (March 18).…”
Section: Relationships Between Soil Water Content and The Co2 Contentmentioning
confidence: 82%
See 4 more Smart Citations
“…However, previous studies that examined the annual isotopic cycle (Pla et al, 2016a) The highest CO2 concentration observed as a direct consequence of the rainfall was achieved between March 28 and 29, some days after the last rainfall on March 24. After this last episode, soil VWC started decreasing but always remained higher than the value observed before the first rainfall episode (March 18).…”
Section: Relationships Between Soil Water Content and The Co2 Contentmentioning
confidence: 82%
“…After this event, CO2 concentration inside the cave increased from March 24 to March 29. Under other circumstances, i.e., without rain, the natural CO2 trend inside the cave would have decreased during this period (Pla et al, 2016a(Pla et al, , 2016b. During the studied event, the role of carbonate host rock dissolution as a contributing source of CO2 to the cave air (SerranoOrtiz et al, 2010) is considered to be negligible because little water was observed dripping into the cave after the rainfall event.…”
Section: Relationships Between Soil Water Content and The Co2 Contentmentioning
confidence: 94%
See 3 more Smart Citations